The Influence of Organizational Climate and Leadership on Nurse Performance: A Narrative Review - Patimah Sari Siregar; Elis Anggeria; Tiarnida Nababan (Universitas Prima Indonesia, 2026)
Nurse performance is a crucial determinant of healthcare quality and patient safety. Beyond clinical competence, contextual factors such as organizational climate and leadership styles play a crucial role in shaping professional outcomes. This study aims to synthesize empirical evidence regarding the influence of organizational climate and leadership on nurse performance and to identify the mediating mechanisms between these variables. A narrative review was conducted using a systematic search strategy across four major databases: PubMed, ScienceDirect, ProQuest, and Google Scholar. The search was limited to articles published between 2019 and 2025. Following the PRISMA guidelines, a total of 213 initial articles were screened, resulting in 7 articles that met the inclusion criteria for final thematic analysis. The thematic synthesis identified three key themes: (1) The role of organizational climate in well-being and retention, (2) The impact of leadership styles on performance, and (3) The mediating role of organizational climate. Findings indicate that a supportive organizational climate is significantly associated with reduced burnout and increased intention to stay. Furthermore, transformational leadership was found to be the most effective style for improving patient outcomes, whereas toxic leadership negatively impacts retention. Organizational climate and leadership are fundamental determinants that simultaneously influence nurse performance. Effective leadership cannot function in isolation; it requires a supportive organizational climate to optimize nurse engagement and clinical outcomes. Management strategies should focus on creating a synergistic environment that combines visionary leadership with a constructive work atmosphere.